(untitled) (Indian Journal of Public Health Research & Development, 2026)
Urban green spaces (UGS) are widely recognized for their significant health and well-being benefits. However, recent research highlights increasing disparities in access to these spaces, particularly among disadvantaged groups. This study investigates the accessibility of UGS for disadvantaged community groups in Bhubaneswar, Odisha, India. Methods: Disadvantaged communities, particularly slum settlements, were identified using high-resolution satellite imagery. Data on urban green spaces were sourced from previous studies. A network analysis was conducted in QGIS to delineate Park Service Areas (PSAs) using a 500-meter walking distance threshold from park entry points, assessing the accessibility of urban green spaces. Results: Among Bhubaneswar’s 67 wards, approximately 42 wards demonstrated that only 0–25% of slum areas fall within a 500-meter PSA. In 8 wards, 25–50% of slum areas were covered. Notably, only 9 wards showed 75–100% coverage of slum areas by PSA. These findings reveal a significant deficit in UGS access for slum dwellers and residents of informal settlements. Conclusion: This study underscores the urgent need for spatially equitable planning of urban green spaces. The findings can inform urban planners and landscape designers in optimizing the distribution of green spaces and strategically placing park entry points to enhance accessibility for marginalized communities.